2020
DOI: 10.1177/0954406220922253
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heat treatment on mechanical and tribological properties of aluminum metal matrix composites

Abstract: LM25 aluminum alloy reinforced with 10 wt% of TiB2, WC, and ZrO2 were squeeze cast to investigate the effect of T6 heat treatment on tribo-mechanical properties. Among all, WC-reinforced composite achieved superior mechanical properties at the aging time of 8 h. Microstructural examination performed on all composites and alloy concluded that the presence of WC in T6 LM25 caused reduction of α-Al dendrite size, exhibiting superior properties for this composite. X-ray diffraction analysis conducted on alloy and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…These loose debris form a tribo-layer composition (MML). [64][65] Based on the obtained COF results at 55 N, it is confirmed that the values are in accordance with the tribolayer consisting Fe, Al, and oxides, which is produced out of sliding action over the counter plate. Similar observations are reported during the mono-directional dry sliding action of Al/13wt%B 4 C composites against a phenol-based brake pads.…”
Section: Reciprocating Wear Testingsupporting
confidence: 61%
“…These loose debris form a tribo-layer composition (MML). [64][65] Based on the obtained COF results at 55 N, it is confirmed that the values are in accordance with the tribolayer consisting Fe, Al, and oxides, which is produced out of sliding action over the counter plate. Similar observations are reported during the mono-directional dry sliding action of Al/13wt%B 4 C composites against a phenol-based brake pads.…”
Section: Reciprocating Wear Testingsupporting
confidence: 61%
“…47 The chance between the measured density and theoretical density values display the porosity percentage in produced compositions and may impress the properties the composites. From the density and porosity studies, it can be analyzed that the moderate increase in the theoretical density value is due to the higher density of MgO particles (3.58 g/cm 3 ) than the matrix alloy density (2.96 g/ cm 3 ). Besides, the air entrapment above the melting point and trapped gases inside the agglomerated particulates might be decreased the density and raised the porosity content of the composites.…”
Section: Discussionmentioning
confidence: 99%
“…The composite materials are materials produced to obtain new materials with the desired properties by the combination of various materials. [1][2][3][4] Metal matrix composites (MMCs) are mostly used in space, defense, automotive, and aviation fields, such as space telescopes, platform carrier parts, reflectors, and support parts of space communication devices, due to their lightweight, high specific strength, fatigue resistance, wear resistance and corrosion resistance, and electrical conductivity properties. [5][6][7][8] MMCs are obtained by applying advanced techniques such as stir casting, powder metallurgy, compo-casting, squeeze casting, melting vacuum impregnation, hot pressing, and diffusion welding by adding different reinforcement materials into a metallic phase.…”
Section: Introductionmentioning
confidence: 99%
“…The composite with 4 wt.% Ti exhibited the highest weight loss and showed extensive plastic deformation when examined under electron microscope. Sam et al [ 84 ] reported tribo-mechanical studies on an LM25 composite reinforced with TiB 2 , WC, and ZrO 2 and produced by squeeze-casting. The cast composite was solutionized at 520 °C for about 8 h, followed by aging at 165 °C for 4, 6, and 8 h. The wear tests were conducted as per the RSM model with applied load, sliding speed, and distance ranging from 10–50 N, 1–4 m/s, and 500–2500 m, respectively.…”
Section: Mechanical and Tribological Properties Of Al-based Mmcsmentioning
confidence: 99%